Heterochromatin-mediated association of achiasmate homologs declines with age when cohesion is compromised. - Subramanian, V.V.; Bickel, S.E. (Genetics, 2009)
Normally, meiotic crossovers in conjunction with sister-chromatid cohesion establish a physical connection between homologs that is required for their accurate segregation during the first meiotic division. However, in some organisms an alternative mechanism ensures the proper segregation of bivalents that fail to recombine. In Drosophila oocytes, accurate segregation of achiasmate homologs depends on pairing that is mediated by their centromere-proximal heterochromatin. Our previous work uncovered an unexpected link between sister-chromatid cohesion and the fidelity of achiasmate segregation when Drosophila oocytes are experimentally aged. Here we show that a weak mutation in the meiotic cohesion protein ORD coupled with a reduction in centromere-proximal heterochromatin causes achiasmate chromosomes to missegregate with increased frequency when oocytes undergo aging. If ORD activity is more severely disrupted, achiasmate chromosomes with the normal amount of pericentric heterochromatin exhibit increased nondisjunction when oocytes age. Significantly, even in the absence of aging, a weak ord allele reduces heterochromatin-mediated pairing of achiasmate chromosomes. Our data suggest that sister-chromatid cohesion proteins not only maintain the association of chiasmate homologs but also play a role in promoting the physical association of achiasmate homologs in Drosophila oocytes. In addition, our data support the model that deterioration of meiotic cohesion during the aging process compromises the segregation of achiasmate as well as chiasmate bivalents.